Development of Pop-up Book Learning Media Geography Tectonism Material Model Book Essentials of Geology - Fransisca Novia Lisa Ayu Rachmadani; Sumarmi Sumarmi; Tuti Mutia; Rudi Hartono; Agus Sugiarto; Ramadhani Lausi Mkumbachi (PT. Pena Produktif Kreatif, 2024)
Curriculum changes that occur give teachers skills in developing learning media that meet the needs of the curriculum and can provide an enjoyable learning experience for students. The product developed in this research is a pop-up book geography tectonism material with the Essentials of Geology book model. This research aims to develop pop-up book geography learning media that is practical, effective, valid, and useful in motivating students to learn tectonism material. The product was developed using the ADDIE model, which includes a) analysis, b) design, c) development, d) implementation, and e) evaluation. Based on the needs and material analysis results, the pop-up learning media book geography tectonism material essentials of the geology book model needs to be developed. The material and media expert validation results state that the media is very valid for the learning process, with a total average score of 91.75 and 90 percent. The total average validation obtained through the teacher response questionnaire to the media is 92.5 percent. With these results, it can be concluded that the validity of this media is in the valid category and can be utilized and applied without revision. After the trial was carried out, the results of the media practicality test were 85.5 percent, and the results of the media effectiveness test were 86.25 percent. With these results, it can be concluded that the media is in the practical and effective category. Effective means motivating student learning in studying geospheric phenomena, lithospheric dynamics material, especially tectonism sub-material, and the media can be used without requiring revisions.